2020
DOI: 10.3390/app10062062
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Piezoelectric Transducer-Based Integrated Structural Health Monitoring System for Impact Monitoring and Impedance Measurement

Abstract: Structural health monitoring (SHM) techniques, which are also considered as online nondestructive testing methods, are significant in modern structural engineering due to their ability to guarantee structure safety while reducing maintenance cost. It is often necessary to combine different SHM methods to achieve a more reliable damage detection result. However, the hardware of the SHM systems is usually expensive, bulky, and heavy when they are designed separately. Therefore, this paper proposes a three-layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…The transducers have two functionalities: passive detection of impacts and active damage assessment using guided Lamb waves. Guo et al proposed a piezoelectric transducer-based integrated SHM system for impact monitoring and impedance measurement [ 106 ]. A “scheduling module” method is utilized to schedule the commands to the PZT sensors and transfer their signals to different preprocessing units for impact detecting or EMI measurement.…”
Section: Piezoelectric Sensors For Structural Health Monitoringmentioning
confidence: 99%
“…The transducers have two functionalities: passive detection of impacts and active damage assessment using guided Lamb waves. Guo et al proposed a piezoelectric transducer-based integrated SHM system for impact monitoring and impedance measurement [ 106 ]. A “scheduling module” method is utilized to schedule the commands to the PZT sensors and transfer their signals to different preprocessing units for impact detecting or EMI measurement.…”
Section: Piezoelectric Sensors For Structural Health Monitoringmentioning
confidence: 99%
“…The evaluation board can measure the impedance signatures up to 100 kHz with 512 maximum data points. Due to these distinguishing advantages, much research had been published around this low-cost, on-board SHM system [14][15][16][17][18][19]. For example [20], investigated the influence of the calibration process of the AD5933 on impedance measurements and validated its damage detection ability in carbon fiber reinforced polymer CFRP panels suffering delamination [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, the device uses an analog filter and does not have the option to select cut-off frequency. Guo et al [16] has successfully shown the possibility of digitizing the sensor with microcontroller usage. However, the author uses the IC AD5933, a high precision impedance converter system with inbuilt digital signal processing capabilities.…”
Section: Introductionmentioning
confidence: 99%